Application Internet of Things in Controlling Fan Based Telegram - Febriyana, Karisman; Saepuloh, Asep (Institute Of Advanced Knowledge and Science, 2024)
IoT is a technology that is currently developing. Iot is used to control an electronic device remotely through a certain device. One of the IoT supporting devices for controlling electronic devices is Telegram. This study aims to create an Internet of Things (IoT) Application System in Telegram-Based Fan Control. The method used to create this system is to apply IoT to fans using the Arduino esp8266 which is a wifi module that functions as an additional microcontroller such as Arduino so that it can connect directly to wifi and make TCP/IP connections. This tool is used as a tool to process input data that will be sent to the output device on the system. This system also consists of a relay prototype that is used to control the electric current path on the fan. The results of the study show that smart phones can also be used to control electronic devices such as fans and other electronic devices.